Addressing the Mental and Emotional Health Impacts of COVID-19 on Children and Adolescents: Lessons From HIV/AIDS - Banati, Prerna; Idele, Priscilla (Frontiers in Psychiatry, 2021)
The COVID-19 pandemic has led to lasting mental health and psychosocial consequences just as were experienced with the HIV epidemic. A rapid review of published systematic reviews on HIV/AIDS and mental health outcomes and responses among children and adolescents was used to identify lessons for the COVID-19 pandemic response. The review found that HIV/AIDS responses to promote mental health, prevent ill-health and treat mental health conditions included diverse interventions at the structural or national, community, household and individual levels. Some of these responses can be replicated, others require substantial adaptation, and some can inform development of new innovative offline and online responses to mitigate impact of COVID-19 on mental health of children and adolescents. Programs that mitigate economic impacts including child grants, income generating activities for caregivers, food distribution, health care vouchers, and other economic empowerment interventions can be replicated with minor adjustments. Helplines for vulnerable or abused children and shelters for victims of gender-based violence can be scaled up to respond to the COVID pandemic, with minimal adaptation to adhere to prevention of contagion. Mass media campaigns to combat stigma and discrimination were successfully employed in the HIV response, and similar interventions could be developed and applied in the COVID context. Some programs will need more substantial adjustments. In health facilities, mainstreaming child-sensitive mental health training of frontline workers and task sharing/shifting to community volunteers and social workers as was done for HIV with community health workers, could advance mental illness detection, particularly among abuse victims, but requires adaptation of protocols. At the community and household levels, expansion of parenting programs can help caregivers navigate negative mental health effects on children, however, these are not often operating at scale, nor well linked to services. Programs requiring innovation include converting adolescent and youth safe physical spaces into virtual spaces particularly for at-risk girls and young women; organizing virtual community support groups, conversations, and developing online resources. Re-opening of schools and introduction of health and hygiene policies, provides another opportunity for innovation - to provide mental health and psychosocial support to all children as a standard package of care and practice.